2024
DOI: 10.1029/2023ja031666
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Ionospheric Radial Currents to Subauroral Polarization Streams During Quiet Periods

Hao Xia,
Hui Wang,
Kedeng Zhang
et al.

Abstract: Using 4 years of ionospheric radial current (IRC) from Swarm and ion velocity from the Defense Meteorological Satellite Program, our work investigates the response of IRC to the subauroral polarization streams (SAPS) during the quiet time for the first time. Both noontime (magnetic local time, MLT 11–14) inward and duskside (MLT 18–19) outward IRC get strengthened in amplitude. The noontime inward ΔIRC is attributed to the penetration westward electric field at low‐mid latitudes. It drives the poleward Hall cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…They proposed that the enhanced merging electric field led to daytime eastward (nighttime westward) PPEF, driving equatorward (poleward) Hall current at low latitudes in the E region, resulting in an upward (downward) increase in IRC (see Figure 4 of Zhong et al, 2023). In addition, Xia et al (2024) reported that a westward (poleward) disturbance electric field at low-mid latitudes induced by subauroral polarization streams produces a downward (upward) IRC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They proposed that the enhanced merging electric field led to daytime eastward (nighttime westward) PPEF, driving equatorward (poleward) Hall current at low latitudes in the E region, resulting in an upward (downward) increase in IRC (see Figure 4 of Zhong et al, 2023). In addition, Xia et al (2024) reported that a westward (poleward) disturbance electric field at low-mid latitudes induced by subauroral polarization streams produces a downward (upward) IRC.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have highlighted the significant impact of the equatorial electric field on IRC (Xia et al, 2024;Zhong et al, 2023). However, the direction of electric field perturbation during substorms is a matter of controversy, and the response of IRC to substorm remains unknown.…”
Section: Introductionmentioning
confidence: 99%